ASSESSING THE IMPACT OF GREEN MARKETING STRATEGIES ON ORGANIZATIONAL IDENTITY AND INNOVATION PERFORMANCE: A COMPREHENSIVE ANALYSIS - Ali Majid; Dr. Muhammad Shoaib Farooq (International Journal of Contemporary Issues in Social Sciences, 2024)
The present thesis examines the effect green marketing strategies have on organizational identity and innovation performance. The thesis explores the way environmental marketing strategies create corporate practice and outcomes for sustainability. The dissertation applies a mixed methods design that incorporates structural equation modelling and thematic analysis to investigate the renationalization’s between green marketing strategies, organizational identity and innovation performance among sustainability-oriented medium-large scale enterprises. The results of the quantitate analysis showed that the impact of green marketing strategies on organization identity has long term positive effect on innovation performance. Furthermore, as the mediation analysis show, organization identity was confirmed as a key link in the connection between green marketing strategies and the outcomes of innovation. Each element of organization image and brand image played a partial mediating effect from top to down and goes further from left to right to promise positive and significant pathway. Therefore, as the integration results of hypothesized pathway, they partially account for this phenomenon. In the end, the qualitative results of the case studies proved the conclusions from the previous parts. Furthermore, through explanations and examples of CA concept and FIT model, the researchers provided further possibility and feasibility of this integration. The research highlights the significance of integrating environmental marketing into organizations’ core strategic framework. It argues that a strong environmental identity not only facilitates sustainability efforts but also generates innovation, providing companies with a competitive advantage in the dynamic market context. The findings contribute to both academic insights and practical implications in the arena of strategic management and environmental sustainability.